Blended learning: Maintaining clinical placements for child nursing students during the COVID-19 pandemic. (2nd February 2022) - Ingleson, Hayley; Hunter, Amy
Abstract : Clinical placement is an essential part of nursing education. students undertake 2300 hours of clinical learning throughout the programme (Nursing and Midwifery Council [NMC], 2018: 1 ). Societal and service changes mean creative transformation is needed to develop sustainable placement opportunities (Carolan et al, 2020 ; NHS England, 2021a ). A blended placement was developed and piloted in community-based children's services. The blended placement gave child nursing students the possibility of experiencing services during the COVID-19 pandemic, by utilising digital and virtual opportunities. Students were placed in the 0–19 public health integrated nursing service, and the integrated children's additional needs service. Two cohorts comprising 25 students undertook the placement. Students and practice supervisors were surveyed on completion of the placement. Survey findings demonstrated three aspects of a good placement experience – information provision, perceived learning opportunities and student support. Recommendations for future blended placements include improved timetabling and information provision adaptions to meet student expectations.